SPATIAL LOGIC CONCEPTS - Kudzh, Stanislav; Tsvetkov, Victor (Revista Inclusiones, 2020)
The purpose of this work is to study and systematize spatial logic. The present paper shows the value of spatial logic arising from its various applications. It studies the relationship between mathematical logic and spatial logic. The article shows the similarities and differences between these logics. It is proved in the study that the main advantage of spatial logic is that it makes it possible to understand the semantics, take into account the coordination of spatial objects and solve problems in the conditions of information uncertainty. The article systematizes various types of spatial logic. It describes the concepts of spatial logic that are common to the family of logics and logic-specific. The paper contains an analysis of some typical errors of figurative logic that are found in cartography. The main problems and contradictions in the development of spatial logic are singled out. The effect of granularity in figurative logic is revealed. The article points out the importance of spatial logic for artificial intelligence and robotics.